ANALYSIS OF PRODUCT QUALITY AND SERVICE ON THE ACHIEVEMENT OF CUSTOMER SATISFACTION AT MACEHAT KOFFEE MEDAN - Elyani Elyani; Juliana Juliana; Erwin Harun; Khamo Waruwu; Imtihan Imtihan (SEAN Institute, 2023)
The purpose of this study was to determine the effect of product and service quality on consumer satisfaction at Koffee Macehat Medan. This research was conducted at Koffee Macehat Medan, with a population and sample of 100 people taken by purposive sampling. The data analysis used is descriptive in nature to explain research data and research descriptions, while to analyze quantitative data using a simple Linear Regression analysis tool. The research instrument was a questionnaire with a Likert scale model. The requirements test is carried out to test normality, heteroscedasticity test. The data analysis technique used is multiple regression technique at a significance level of α = 0.05. The results showed: (1) there is a significant influence between product quality on consumer satisfaction with t count = 2.201; (2) there is a significant effect between Service on Consumer Satisfaction with t count = 2.498. The suggestions made are; (1).Koffee Macehat further enhances the excellent service for its customers in order to provide a sense of comfort so that it can be sustainable. (2) Adding a variety of coffee flavors so that customers don't get bored with the monotonous taste, at least make it more interesting to make it more interesting. (3). Creating a comfortable place so that consumers who come and visit feel satisfied and feel at home so that they increase their purchasing portion